1992
DOI: 10.1099/0022-1317-73-4-901
|View full text |Cite
|
Sign up to set email alerts
|

Bovine coronavirus uses N-acetyl-9-O-acetylneuraminic acid as a receptor determinant to initiate the infection of cultured cells

Abstract: The importance of N-acetyl-9-O-acetylneuraminic acid (Neu5,9Ac2) as a receptor determinant for bovine coronavirus (BCV) on cultured cells was analysed. Pretreatment of MDCK I (Madin Darby canine kidney) cells with neuraminidase or acetylesterase rendered the cells resistant to infection by BCV. The receptors on a human (CaCo-2) and a porcine (LLC-PK1) epithelial cell line were also found to be sensitive to neuraminidase treatment. The susceptibility to infection by BCV was restored after resialylation of asial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
84
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 23 publications
1
84
1
Order By: Relevance
“…First, it is able to mediate attachment of the virus to the cell surface and the fusion of cell and virus membranes (Collins et al, 1982;Vennema et al, 1990a). Recent evidence suggests that these functions also involve a cell surface receptor, a member of the carcinoembryonic antigen family (Dveksler et al, 1991;Williams et al, 1991) and that post-translational modifications of the receptor, possibly glycosylation, are required (Pensiero et al, 1992; see also Schultze et al, 1991 ;Schultze & Herrler, 1992). Second, I Present address: Immuno Research Centre, Uferstrasse 15, A-2304 Orth/Donau, Austria.…”
Section: Introductionmentioning
confidence: 99%
“…First, it is able to mediate attachment of the virus to the cell surface and the fusion of cell and virus membranes (Collins et al, 1982;Vennema et al, 1990a). Recent evidence suggests that these functions also involve a cell surface receptor, a member of the carcinoembryonic antigen family (Dveksler et al, 1991;Williams et al, 1991) and that post-translational modifications of the receptor, possibly glycosylation, are required (Pensiero et al, 1992; see also Schultze et al, 1991 ;Schultze & Herrler, 1992). Second, I Present address: Immuno Research Centre, Uferstrasse 15, A-2304 Orth/Donau, Austria.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it appears that the HE of BCV is important in virus infectivity. In addition to the S glycoprotein which has strong receptor-binding properties [20,23,24], binding of the HE glycoprotein of the short peplomers to Nacetyl-9-O-acetylneuraminic acid residues on the cell surface may function as a pre-receptor interaction for BCV. However, the HE of mouse hepatitis virus strains A59 and JHM is not expressed in productive infections, and thus is not essential for replication of these strains [25].…”
Section: Introductionmentioning
confidence: 99%
“…Enzymic removal of the N-acetyl-9-O-acetylneuraminic acid residue from cell membranes or treatment with HEspeci®c monoclonal antibodies (MAbs) inhibits BCV infections [19,20]. Furthermore, cells infected with a recombinant baculovirus expressing the HE of BCV exhibited haemadsorption and esterase activities, both of which could be blocked by MAbs with infectivity neutralisation activity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of influenza C virus, the importance of the receptor-destroying enzyme has been studied using sialic acid analogues. Some of these artificial sialic acids can function as receptor determinants but are resistant to the receptordestroying enzyme (Herrler et al, 1992). With this approach, it has been shown that the acetylesterase is required to keep the virus surface free of receptor determinants, which otherwise would result in a decrease of the infectious virus titre due to aggregate formation (Ho$ fling et al, 1996).…”
mentioning
confidence: 99%
“…Viruses of the genus Paramyxovirus as well as influenza A and B viruses recognize N-acetylneuraminic acid (Neu5Ac) and inactivate their receptors by a sialidase (neuraminidase) that releases terminal sialic acid from glycoconjugates (Klenk et al, 1955). Influenza C virus and several coronaviruses require a different type of sialic acid for binding to cells, N-acetyl-9-O-acetylneuraminic acid (Herrler & Klenk, 1987 b ;Rogers et al, 1986 ;Schultze & Herrler, 1992). Their receptor-destroying enzyme is an acetylesterase that releases the 9-O-acetyl group from the receptor determinant (Herrler et al, 1985 c ;.…”
mentioning
confidence: 99%